Controls on explosive-effusive volcanic eruption styles - Mike Cassidy (Nature Portfolio, 2018)
Eruptive styles at a single volcano may transition from explosive to effusive behaviour (or vice versa) at any given time. This review examines the underlying controls on eruptive styles such as magma viscosity, degassing and conduit geometry at volcanoes with silicic compositions.